Pengaruh Struktur Modal, Ukuran Perusahaan dan Keputusan Investasi terhadap Nilai Perusahaan - Rossabela Dwita; Kurniawan Kurniawan (Universitas Matana, 2019)
The purpose of this research was to determine the effect of Capital Structure measured using debt to assets ratio (DAR), firm size measured using total assets and investment decisions measured using price earnings ratio (PER) to firm value measured using price book value (PBV). in financial sector companies listed on the Indonesia Stock Exchange (IDX) period 2013-2016.The type of research was causal research. The population in this research is financial sector companies listed on the Indonesia Stock Exchange (IDX) period 2013-2016.. Sampling technique that used in this study was purposive sampling technique. Of the population of 95 financial sector companies obtained Sample amounted to 49 companies of the financial sector listed on the Indonesia Stock Exchange in 2013-2016, so that the data analyzed research amounted to 196 observations. Data analysis techniques use multiple linear regression.Based on the results of this study indicate that the Capital Structure has a negative and significant effect on the Company Value with t value of -3.128 and the significance value smaller than 0.05 is 0.002. The size of the company has a positive effect on the value of the company with a value of t arithmetic of 3.524 and the value of significance smaller than 0.05 is 0.001. Investment Decision has a positive effect on the company's value with t value of 5.914 and significance value smaller than 0.05 ie 0.000.